MODERNISATION ISSUES OF GENDER AND SPACE - Titien Saraswati (DIMENSI (Journal of Architecture and Built Environment), 2000)
Jurgen Habermas proposes a theory of modernisation based on the notion of a progressive "uncoupling" or separation of some aspects of everyday life, and their take over or "colonisation" by an expanding state and formal economy. This model is criticised by Nancy Fraser on the basis that it ignores the place of gender in the various roles that the individual plays in society and which mediate between the world of everyday life and the "system world" of the state and the official economy. Habermas's argument is further criticised for ignoring the issue of space (the house, the neighbourhood) in that mediation. Further, Habermas and also Fraser arguments however yield to what they call symbolic reproduction and material reproduction, socially integrated action contexts and system integrated action contexts, and also private sphere and public sphere. The above terms will be elaborated more fully in this paper.